Prognostic Value of Plasma Cold-Inducible RNA-Binding Protein in Patients with Acute Coronary Syndrome. (27th April 2022) - Ren, Xiaomin; Xie, Hao; Zhang, Juan; Jin, Xiaoping; Cui, Lianqun; Chen, Liming; Chen, Liang; Zuo, Guangfeng
Abstract : Background . Cold-inducible RNA-binding protein (CIRP) is a proinflammatory cytokine. The Global Registry of Acute Coronary Events (GRACE) risk score has been widely applied in risk stratification in patients with acute coronary syndrome (ACS). We aimed to investigate the prognostic value of CIRP in ACS patients and its incremental prognostic performance on top of GARCE score. Methods . We consecutively enrolled 320 ACS patients, including 128 patients with ST-elevation myocardial infarction (STEMI), 67 patients with non-ST-elevation myocardial infarction (NSTEMI), and 125 patients with unstable angina pectoris (UAP). Plasma CIRP levels were measured at baseline. All patients received one-year follow-up for occurrence of major adverse cardiovascular outcomes (MACEs). Results . STEMI patients had a significantly higher concentration of plasma CIRP than those with NSTEMI (p = 0.001 ) and UAP (p < 0.001 ). Plasma CIRP level was positively correlated with GRACE score (r = 0.40, p < 0.01 ). Survival analysis revealed that the risk of MACEs increased with increasing CIRP level (log-rank p < 0.001 ). During follow-up, 45 (14.1%) patients experienced MACEs. Both GRACE score (hazard ratio: 1.023, 95% confidence interval: 1.007-1.050, p = 0.021 ) and plasma CIRP level (hazard ratio:1.800, 95% confidence interval:1.209-2.679, p = 0.004 ) were independently predictive of MACEs after Cox multivariate adjustment. Incremental predictive value was observed after combining CIRP with GRACE score. Conclusions . Plasma CIRP was an independent prognostic biomarker and could improve the predictive value of GRACE score for prognosis in ACS patients.